Assessment strategies for municipal selective waste collection schemes. (January 2017) - Ferreira, Fátima; Avelino, Catarina; Bentes, Isabel; Matos, Cristina; Teixeira, Carlos Afonso
Highlights: Performance assessment of MSW selective collection schemes. Statistical analysis based on performance indicators. Proposal of a global performance index of selective collection schemes. Validation using Oporto Municipality as a case study. Abstract: An important strategy to promote a strong sustainable growth relies on an efficient municipal waste management, and phasing out waste landfilling through waste prevention and recycling emerges as a major target. For this purpose, effective collection schemes are required, in particular those regarding selective waste collection, pursuing a more efficient and high quality recycling of reusable materials. This paper addresses the assessment and benchmarking of selective collection schemes, relevant to guide future operational improvements. In particular, the assessment is based on the monitoring and statistical analysis of a core-set of performance indicators that highlights collection trends, complemented with a performance index that gathers a weighted linear combination of these indicators. This combined analysis underlines a potential tool to support decision makers involved in the process of selecting the collection scheme with best overall performance. The presented approach was applied to a case study conducted in Oporto Municipality, with data gathered from two distinct selective collection schemes.